PENGATURAN PERUSAHAAN DAERAH AIR MINUM DALAM PENGELOLAAN AIR MINUM DI KOTA KUPANG - Foenay, Jeniefer Gita Marchlina; Yohanes, Saryono; Ratu Udju, Hernimus (Petitum Law Journal, 2024)
The current policy taken by the Government is an effort to expand the water network to reach Kupang City residents who are not yet connected to the Kupang City PDAM water network. The aim of conducting research: To find out and analyze the Drinking Water Supply System Management Arrangements at Regional Drinking Water Companies in Kupang City and to find out and analyze the Drinking Water Supply System Management Arrangement Factors at Regional Drinking Water Companies in Kupang City. To answer this problem, Normative Research was carried out which was supported by Empirical Juridical Research, namely, examining the real behavior of Regional Drinking Water Companies based on facts or realities obtained in the field for further research. The results of this research show that this research states that the Drinking Water Supply System (SPAM) was implemented to provide drinking water services to the people of Kupang City to meet drinking water needs, namely, the availability of drinking water services to fulfill people's rights to drinking water and the realization of water management and services. quality drinks at affordable prices. Based on research in the field, water leaks can reach more than 30.7% of the existing water supply (production). Determination of water needs is carried out by water leak analysis. The water leak reduction program needs to be improved so that the balance of service flow is not disturbed. The conclusion is that the arrangements for managing the Drinking Water Supply System at the Regional Drinking Water Company in Kupang City do not meet the proper standards, from management to distribution of Drinking Water, there are traffic jams in distribution and problems with several damaged pipes and inadequate service. Inhibiting factors for the Drinking Water Supply Management System, namely: Late payments, information that customers ignore.